COSMIC RAY INTENSITY VARIATIONS DURING 1963. - Sandstrom,A. E.; Dyring,E.; Ekstrom,L.; Gronkvist,B. O.; Lindgren,S. (1964)
During 1963 the recorders have continued in Uppsala and Kiruna by one neutron monitor, two cubical telescopes and six inclined telescopes. Tables and figures give a detailed account of diurnal and semidiurnal variations during the year. A sharp phase shift in the semidiurnal variation can be found for the neutron monitor. Five decreases are illustrated by bihourly diagrams. (Author)